Study on the Deflection Calculation of a Steel Truss Web–Concrete Composite Beam Under Pre-Stress - Chunmei Ni; Xiaowei Liu; Zhilong Wang; Sheng Li (Buildings)
The aim of this study is to establish an accurate calculation method for the deflection caused by the effect of pre-stress in a steel truss web–concrete composite girder bridge based on the energy variational principle, considering the influence of shear deformation and the shear lag effect of the steel truss web member on the accuracy of the deflection calculation. The pre-stress effect is determined by the equivalent load method, and the deflection analytical solution for a composite girder bridge under straight-line, broken-line, and curve pre-stressing tendon arrangements is established. The reliability of the formula is verified using ANSYS 2022 finite element numerical simulation. At the same time, the influence of shear deformation, the shear lag effect, and their combined (dual) effect on the deflection calculation accuracy is analyzed under different linear pre-stressed reinforcement arrangements and comprehensive arrangements of pre-stressed reinforcement. The analysis of the example shows that the analytical solution for the deflection of the steel truss web–concrete composite beam, when considering only the shear deformation and the dual effect, is more consistent with the finite element numerical solution. The shear deformation of the steel truss web member under the eccentric straight-line arrangement alone does not cause additional deflection, and the additional deflection caused by the shear lag effect can be ignored. The influence of shear deformation on deflection is higher than that of the shear lag effect. The contribution ratio of the additional deflection caused by the dual effect is greater than 14%, and the influence of the dual effect on deflection is more obvious under a broken-line arrangement. Under the comprehensive arrangement of pre-stressing tendons, the contribution rate of shear deformation to the total deflection is about 3.5 times that of shear lag. Compared with the deflection value of the primary beam, the mid-span deflection is increased by 3.0%, 11.0%, and 13.9% when only considering the shear lag effect, only considering shear deformation, and considering the dual effect, respectively. Therefore, shear deformation and the shear lag effect should be considered when calculating the camber of a steel truss web–concrete composite girder bridge to improve the calculation accuracy.